The Effect of Electronic Word of Mouth, Emotional Branding and Brand Characteristic on Fashion Product Purchasing Decisions in E-commerce Platform - Farizy, Noercholis; Harsoyo, Titik (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to analyze the influence of electronic word of mouth, emotional branding, and brand characteristics on purchasing decisions for Erigo products on Shopee e-commerce. The independent variables include electronic word of mouth, emotional branding, and brand characteristics, with purchasing decisions as the dependent variable. Employing a causal quantitative approach, data collection involved distributing questionnaires to 100 respondents who had previously made purchases on e-commerce. All questionnaire items for the variables demonstrated validity and reliability. Classical assumption tests indicated normally distributed data, a regression model free from multicollinearity, and the absence of heteroscedasticity. The research findings reveal that electronic word of mouth, emotional branding, and brand characteristics all have positive and significant effects on purchasing decisions, implying that these factors play crucial roles in shaping consumer choices.